2023
DOI: 10.3390/land12020434
|View full text |Cite
|
Sign up to set email alerts
|

Why Did the “Missing Middle” Miss the Train? An Actors-In-Systems Exploration of Barriers to Intensified Family Housing in Waterloo Region, Canada

Abstract: (1) Background: Missing Middle (MM) housing may be critical to address decreasing housing affordability and to achieve critical density in transit-oriented neighborhoods; however, its production is in decline. We report on a case study of housing development around a new light-rail transit line in the Region of Waterloo, Canada, investigating the puzzle of how a residential building boom coincided with decreasing housing affordability. (2) Methods: Following participatory co-creation and communication of backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…For the variables of interest (transit-related variables), we found that properties within the central transit corridor (CTC) were about 1.4% higher in price (based on the median estimate from GWR), suggesting that people were willing to pay more for living in the CTC even when the LRT was under construction. This evidence supports that TOD has been seen as an urban amenity in our case-study region, if not for every household, for many and diverse households (Huang et al, 2021;Parker et al, 2023). The result also confirms our hypothesis that strong preferences for TOD in KW existed in anticipation of LRT.…”
Section: Gwr Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…For the variables of interest (transit-related variables), we found that properties within the central transit corridor (CTC) were about 1.4% higher in price (based on the median estimate from GWR), suggesting that people were willing to pay more for living in the CTC even when the LRT was under construction. This evidence supports that TOD has been seen as an urban amenity in our case-study region, if not for every household, for many and diverse households (Huang et al, 2021;Parker et al, 2023). The result also confirms our hypothesis that strong preferences for TOD in KW existed in anticipation of LRT.…”
Section: Gwr Resultssupporting
confidence: 89%
“…They prefer to build denser, more compact projects and see obstacles to realizing affordable family housing, particular with regards to financing projects (Guthrie and Fan, 2016). In KW, evidence from other case-study research indicates a corresponding supply deficit of suitable housing along the corridor for larger households with low-to-moderate incomes (Parker et al, 2023). The authors hypothesize that complex interactions between developer and investor expectations and planning changes have “locked in” small-unit high-rise development and “locked out” provision of “Missing Middle” (MM) housing supply—medium-density housing types that fall between the scales of single-family homes and high-rise apartments, which can provide desirable home options for larger families (Parker et al, 2023).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations